Formulasi Dan Uji Aktifitas Nanoemulsi Minyak Atsiri Daun Kemangi (Ocimum basilicum L.) Terhadap Salmonella typhi - Monica Kristiani; Septiana Laksmi Ramayani; Klara Yunita; Meilina Saputri (Jurnal Farmasi Indonesia, 2019)
Essential oil of basil (Ocimum basilicum L.) leaves with a concentration of 2.5% can be estimated to have a diameter of inhibition zone with an average value of 8.67 ± 0.58 mm. Essential oils have volatile characteristics, and are easily oxidized so that they can affect their activities as antibacterial. To increase stability, essential oils of basil leaves need to be packaged in a special delivery system. Nanoemulsion is made by spontaneous emulsification method. Nanoemulsion was further tested for physical characteristics including droplet size, polydispersity index, zeta potential and nanoemulsion morphology using a Transmission Electron Microscope (TEM). The preparation was then tested for its activity against Salmonella thypi. The method used is the Kirby-Bauer disk diffusion method. From the test of physical characteristics obtained the average particle size of 10.6 nm, polydispersity index 0.03 and zeta potential -36.4. The results of the observation using TEM form the particles produced are spherical. Antibacterial test results were shown by the formation of inhibition zones of basil leaf essential oil (9.3 mm), positive control (6.6 mm), negative control (7.5 mm), nanoemulsion of basil leaf essential oil (8.3 mm), Virgin Coconut Oil (7 mm). Based on the results of statistical analysis it was found that there were no significant differences in treatment between groups.